The female syndecan-4−/− heart has smaller cardiomyocytes, augmented insulin/pSer473-Akt/pSer9-GSK-3β signaling, and lowered SCOP, pThr308-Akt/Akt and GLUT4 levels - Støle, Thea Parsberg; Lunde, Marianne; Shen, Xin; Martinsen, Marita; Lunde, Per Kristian; Li, Jia; Lockwood, Francesca; Sjaastad, Ivar; Louch, William Edward; Aronsen, Jan Magnus; Christensen, Geir; Carlson, Cathrine Rein (Frontiers in Cell and Developmental Biology, 2022)
Background: In cardiac muscle, the ubiquitously expressed proteoglycan syndecan-4 is involved in the hypertrophic response to pressure overload. Protein kinase Akt signaling, which is known to regulate hypertrophy, has been found to be reduced in the cardiac muscle of exercised male syndecan-4−/− mice. In contrast, we have recently found that pSer473-Akt signaling is elevated in the skeletal muscle (tibialis anterior, TA) of female syndecan-4−/− mice. To determine if the differences seen in Akt signaling are sex specific, we have presently investigated Akt signaling in the cardiac muscle of sedentary and exercised female syndecan-4−/− mice. To get deeper insight into the female syndecan-4−/− heart, alterations in cardiomyocyte size, a wide variety of different extracellular matrix components, well-known syndecan-4 binding partners and associated signaling pathways have also been investigated. Methods: Left ventricles (LVs) from sedentary and exercise trained female syndecan-4−/− and WT mice were analyzed by immunoblotting and real-time PCR. Cardiomyocyte size and phosphorylated Ser473-Akt were analyzed in isolated adult cardiomyocytes from female syndecan-4−/− and WT mice by confocal imaging. LV and skeletal muscle (TA) from sedentary male syndecan-4−/− and WT mice were immunoblotted with Akt antibodies for comparison. Glucose levels were measured by a glucometer, and fasting blood serum insulin and C-peptide levels were measured by ELISA. Results: Compared to female WT hearts, sedentary female syndecan-4−/− LV cardiomyocytes were smaller and hearts had higher levels of pSer473-Akt and its downstream target pSer9-GSK-3β. The pSer473-Akt inhibitory phosphatase PHLPP1/SCOP was lowered, which may be in response to the elevated serum insulin levels found in the female syndecan-4−/− mice. We also observed lowered levels of pThr308-Akt/Akt and GLUT4 in the female syndecan-4−/− heart and an increased LRP6 level after exercise. Otherwise, few alterations were found. The pThr308-Akt and pSer473-Akt levels were unaltered in the cardiac and skeletal muscles of sedentary male syndecan-4−/− mice. Conclusion: Our data indicate smaller cardiomyocytes, an elevated insulin/pSer473-Akt/pSer9-GSK-3β signaling pathway, and lowered SCOP, pThr308-Akt/Akt and GLUT4 levels in the female syndecan-4−/− heart. In contrast, cardiomyocyte size, and Akt signaling were unaltered in both cardiac and skeletal muscles from male syndecan-4−/− mice, suggesting important sex differences.